Księgi w kurii diecezjalnej w aspekcie kanonicznym - Jerzy Adamczyk (Wrocławski Przegląd Teologiczny, 2019)
Maintenance and storage of books in the bishop's curia constitute an important part of church administration. This article addresses the canonical aspect of such books.First, the provisions of the Code on the need to maintain specific registers in the curia were first introduced. Second, the books necessary for the proper management of the diocese in the curia are presented.Next, the books for the registration of certain facts of legal importance are discussed. Finally, the focus has been put on the books in force under the specific law.